2019
DOI: 10.20996/1819-6446-2019-15-4-502-509
|View full text |Cite
|
Sign up to set email alerts
|

Doctors’ Adherence to the Guidelines on the Diagnostics and Treatment of Arterial Hypertension

Abstract: Aim. Examination of knowledge of the basic provisions of clinical guidelines for the management of patients with arterial hypertension and finding out the readiness of doctors for the practical application of updated recommendationsMaterial and methods. Anonymous questionnaires of 306 doctors served as material for the study. The questionnaire consisted of two parts. The introductory part included questions that allow to find out the specialty, work experience, gender, age, and whether the respondent has cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
2
0
2
Order By: Relevance
“…Основными критериями исследований приверженности врачей КР являются выбор и назначение ЛП с доказанной эффективностью, достижение целевых дозировок (например, у пациентов с хронической сердечной недостаточностью), целевых значений ряда показателей (артериального давления, холестерина липопротеинов низкой плотности, международного нормализованного отношения, гликированного гемоглобина и др.) [2,13,[23][24][25][26].…”
Section: результатыunclassified
“…Основными критериями исследований приверженности врачей КР являются выбор и назначение ЛП с доказанной эффективностью, достижение целевых дозировок (например, у пациентов с хронической сердечной недостаточностью), целевых значений ряда показателей (артериального давления, холестерина липопротеинов низкой плотности, международного нормализованного отношения, гликированного гемоглобина и др.) [2,13,[23][24][25][26].…”
Section: результатыunclassified
“…Недостаточная результативность антигипертензивной терапии (АГТ) может быть связана с неточной диагностикой, неверной стратификацией рисков [4], погрешностями измерения артериального давления (АД), резистентностью к терапии [5]. Одной из наиболее распространенных причин неэффективности лечения является несоблюдение рекомендаций по лекарственной терапии и коррекции образа жизни, что, зачастую, остается не выявленным [6,7].…”
Section: Introductionunclassified
“…Mainly, the reason to update educational programs is the publication of the next edition of clinical guidelines for the diagnosis and treatment of this or that disease approved by the Scientific and Practical Council of the Ministry of Health of the Russian Federation. These documents must be revised at least once every three years 6 . Updating the content of educational programs often requires correcting the ratio of time spent on considering individual topics within the approved forms of information presentation.…”
mentioning
confidence: 99%
“…Another survey was devoted to the study of doctors' adherence to recommendations on the diagnosis and treatment of arterial hypertension [6]. As a result of this work, it was found that doctors do not give due weight to the cardiovascular events risk stratification in patients with arterial hypertension and are not sufficiently aware of the possibilities and limitations of the use of antihypertensive drugs combinations.…”
mentioning
confidence: 99%